1990
DOI: 10.1093/nar/18.12.3503
|View full text |Cite
|
Sign up to set email alerts
|

DNasel hypersensitive sites 1, 2 and 3 of the human β-globin dominant control region direct position-independent expression

Abstract: The human beta-globin dominant control region (DCR) which flanks the multigene beta-globin locus directs high level, site of integration independent, copy number dependent expression on a linked human beta-globin gene in transgenic mice and stably transfected mouse erythroleukemia (MEL) cells. We have assayed each of the individual DNaseI hypersensitive regions present in the full 15kb DCR for position independence and copy number dependence of a linked beta-globin gene in transgenic mice. The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
1
3

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(122 citation statements)
references
References 30 publications
4
114
1
3
Order By: Relevance
“…In transgenic mice 5' HS 1-5 sites enhance the expression of a linked j-globin gene 300-fold (8,9). Individual sites 5' HS 2, 5' HS 3 and 5' HS 4 activate expression approximately 100 fold in transgenic animals and 5' HS 1 lacks significant activity (9)(10)(11)(12)(13); the 5' HS 5 site may contain a domain boundry sequence that insulates globin gene family members from effects of upstream regions (14). The importance of sites 5' HS GenBank accession no.…”
Section: Introductionmentioning
confidence: 99%
“…In transgenic mice 5' HS 1-5 sites enhance the expression of a linked j-globin gene 300-fold (8,9). Individual sites 5' HS 2, 5' HS 3 and 5' HS 4 activate expression approximately 100 fold in transgenic animals and 5' HS 1 lacks significant activity (9)(10)(11)(12)(13); the 5' HS 5 site may contain a domain boundry sequence that insulates globin gene family members from effects of upstream regions (14). The importance of sites 5' HS GenBank accession no.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that the activity of the LCR resides in these hypersensitive site (HS) regions and identified the core elements as 200-300 bp fragments [10][11][12][13][14]. There is strong evidence suggesting that each HS retains the essential properties of the LCR, although each site varies with regard to the level of transcriptional stimulation per gene and its developmental specificity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we have focussed our attention on the core fragment of HS3, which is transcriptionally the most active individual site of the LCR [15,17]. It is a 225 bp fragment which we have functionally defined in both transgenic mice and murine erythroleukemia (MEL) cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this model the complete LCR plays a pivotal role in gene competition. This is supported by the fact that no individual HS of the LCR provides full expression to a linked globin gene (Fraser et al 1990(Fraser et al , 1993, and that all sites are required in the context of the full locus for high-level, position-independent expression (Milot et al 1996). The competitive advantage of an individual gene is achieved through proximity to the LCR and the specific transacting factor environment of a particular developmental stage.…”
mentioning
confidence: 99%